2021
DOI: 10.1007/s11256-021-00601-6
|View full text |Cite
|
Sign up to set email alerts
|

School Choice, Exclusion, and Race Taming in Milwaukee: A Meta-ethnography

Abstract: This article presents a meta-ethnography (Urrieta Jr and Noblit (eds), Cultural constructions of identity: meta ethnography and theory, Oxford University Press. 2018. 10.1093/oso/9780190676087.001.0001) of school choice across education sectors in Milwaukee, Wisconsin, USA. A site of intense contention and experimentation around school choice, Milwaukee constitutes a unique case that can offer insights into similar education reforms increasingly being implemented on a global scale. In synthesizing six book-len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Biological PPI networks belong to the category of the “scale-free” or “small-world” networks, which are neither completely regular (i.e., networks, where each node has exactly the same number of links) or completely random ( Erdös and Rényi, 1960 ). An example of the random networks is given by the highway system, in which despite the random placement of links most nodes have approximately same number of links ( Erdös and Rényi, 1960 ; Barabasi and Bonabeau, 2003 ). Because the nodes follow a Poisson distribution with a bell shape, such a system almost do not have nodes that have significantly more or fewer links than the average ( Barabasi and Bonabeau, 2003 ).…”
Section: Network Of Network: From Single Proteins To Protein-protein Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological PPI networks belong to the category of the “scale-free” or “small-world” networks, which are neither completely regular (i.e., networks, where each node has exactly the same number of links) or completely random ( Erdös and Rényi, 1960 ). An example of the random networks is given by the highway system, in which despite the random placement of links most nodes have approximately same number of links ( Erdös and Rényi, 1960 ; Barabasi and Bonabeau, 2003 ). Because the nodes follow a Poisson distribution with a bell shape, such a system almost do not have nodes that have significantly more or fewer links than the average ( Barabasi and Bonabeau, 2003 ).…”
Section: Network Of Network: From Single Proteins To Protein-protein Interactionsmentioning
confidence: 99%
“…An example of the random networks is given by the highway system, in which despite the random placement of links most nodes have approximately same number of links ( Erdös and Rényi, 1960 ; Barabasi and Bonabeau, 2003 ). Because the nodes follow a Poisson distribution with a bell shape, such a system almost do not have nodes that have significantly more or fewer links than the average ( Barabasi and Bonabeau, 2003 ). Topology of the PPI networks (as well the airline routes, the author-collaboration network, the metabolic network, gene network, the protein domain network, social networks, and the World Wide Web) is different, as they have hubs, with many connections, and ends, that aren’t connected to anything but a hub ( Watts and Strogatz, 1998 ; Goh et al, 2002 ).…”
Section: Network Of Network: From Single Proteins To Protein-protein Interactionsmentioning
confidence: 99%
“…If neurobiology gets and stays different through exposure, we ask here how much of it gets gendered too, by virtue of its material and relational constitution. And if it does, how can we incorporate a wider and sharper scope of social, political and biological agents into our analyses where matter and mattering are taken seriously “against the limits” of representational or constructionist paradigms ( Grosz, 1994 ; Pitts-Taylor, 2016 ). We find this a pressing and timely task, not only as it points to generative possibilities for collaborative research, but also because of the ripple effects neuroepigenetic research may have in other nascent fields.…”
Section: Neuroepigenetics: Neurobiological Change and Memorymentioning
confidence: 99%
“…Human genetic diversity is a continuum, which means that there are no fixed, immutable or discrete boundaries between populations. Linguistic, geographic and social factors can lead to different demographic histories and, in turn, to patterns of inter-population variability ( Lao et al, 2008 ; Barbujani et al, 2013 ; Batai et al, 2020 ; Heyer and Reynaud-Paligot, 2020 ). It has been previously reported that this stratification has consequences in the genetics of complex traits and diseases [reviewed in Bentley et al (2017) ; Sirugo et al (2019) ].…”
Section: Introductionmentioning
confidence: 99%